Ultra-frequent HRAS p.Q61R somatic mutation in canine acanthomatous ameloblastoma reveals pathogenic similarities with human ameloblastoma - Peralta S.; McCleary-Wheeler A.L.; Duhamel G.E.; Heikinheimo K.; Grenier J.K. (WILEY, 2022)
Ameloblastoma is a locally aggressive odontogenic tumour that occurs in humans and dogs. Most ameloblastomas (AM) in humans harbour mutually-exclusive driving mutations in BRAF, HRAS, KRAS, NRAS or FGFR2 that activate MAPK signalling, and in SMO that activates Hedgehog signalling. The remarkable clinical and histological similarities between canine acanthomatous ameloblastoma (CAA) and AM suggest they may harbour similar driving mutations. In this study, aimed at characterizing the mutational status of SMO, BRAF, HRAS, KRAS, NRAS and FGFR2 in CAA, we used RNA sequencing, Sanger sequencing and restriction fragment length polymorphism assays to demonstrate that 94% of CAA (n = 16) harbour a somatic HRAS p.Q61R mutation. The similarities in MAPK-activating mutational profiles between CAA and AM implicate conserved molecular mechanisms of tumorigenesis, thus, qualifying the dog as a potentially useful model of disease. Given the relevance of RAS mutations in the pathogenesis of odontogenic tumours and other types of cancer, the results of this study are of comparative, translational, and veterinary value.